Pengaruh Kegiatan Didikan Subuh Terhadap Pengetahuan Dasar Islam Pada Siswa Sekolah Dasar - Santhy Wisuda Sidauruk; Sri Yuliana; Chinta Adelia Pertiwi; Akil Mariza Putera; Tiara Syafitri; Disa Putri Anggianti; Widya Dwi Jayanti; Azza Ayumi; Risniya Risniya; Rendra Gustian; Yoga Pratama Nasution (BADAN PENERBIT STIEPARI PRESS, 2023)
Education is an important aspect of the development process in a country. In today's digital era, the basic knowledge of Islam in children is quite minimal. This can be seen directly from the didikan subuh activities that we have carried out, that most of the children still do not know about the basic knowledge of Islam, such as the pillars of Islam, the pillars of faith, the names of angels and their duties, daily prayers, and short surahs in the Koran. Based on this, our didikan subuh activity aims to provide basic Islamic knowledge to children in Tanjung Damai Village. The children involved are students of SDN 20 Siak Kecil. The method we use to deliver the material is by using infocus as a medium to attract children's attention. In addition, we also formed several groups to make learning more interactive. Through this activity, the results that have been achieved are the increase in children's knowledge about the basis of Islam.